2015
DOI: 10.1161/atvbaha.114.304748
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Minor Lysophospholipids in the Increase in Plasma Lysophosphatidic Acid in Acute Coronary Syndrome

Abstract: Objective-Lysophosphatidic acids (LPA) have important roles in the field of vascular biology and are derived mainly from lysophosphatidylcholine via autotaxin. However, in our previous study, only the plasma LPA levels, and not the serum autotaxin levels, increased in patients with acute coronary syndrome (ACS). The aim of this study was to elucidate the pathway by which LPA is increased in patients with ACS. Approach and Results-We measured the plasma lysophospholipids species in 141 consecutive patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 41 publications
(49 reference statements)
6
83
1
Order By: Relevance
“…Our results indicated that endothelia exposed to disturbed flow are primed to LPA stimulation which might be further augmented by additional atherogenic factors since LPA is produced during mild oxidation of LDL and accumulates in human atherosclerotic plaques 25 . Recently, plasma long-chain unsaturated LPA was reported to be elevated in patients with acute coronary syndrome 26 . Indeed, our data demonstrate a sensitized inflammation in PPAP2B-deficient cells treated with LPA but not TNFα.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that endothelia exposed to disturbed flow are primed to LPA stimulation which might be further augmented by additional atherogenic factors since LPA is produced during mild oxidation of LDL and accumulates in human atherosclerotic plaques 25 . Recently, plasma long-chain unsaturated LPA was reported to be elevated in patients with acute coronary syndrome 26 . Indeed, our data demonstrate a sensitized inflammation in PPAP2B-deficient cells treated with LPA but not TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal activation of LPA signaling is implicated in various human diseases such as cancer, fibrotic disorders, metabolic syndrome, and cardiovascular diseases 22-24 . LPA accumulates in human atherosclerotic plaques 25 and plasma LPA is elevated in patients with acute coronary syndrome 26 . In ApoE-deficient mice, systemic inhibition of LPA receptors employing pharmacological antagonists notably reduced the atherosclerotic burden 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of LPLs in chronic inflammatory disorders such as coronary artery disease (CAD), hypertension [18,19], atherosclerosis and severe vascular diseases is well established [20,21]. Furthermore, LPLs contribute to pathophysiology of autoimmune disorders such as rheumatoid arthritis, and is involved in exacerbating the progression of the disease [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Human plasma was reported to contain phosphatidylglycerol at about 300 nM [33], and LPG at about 250 nM [34]. It should be mentioned that evidence for LPG acyltransferase 1 as having the strongest association with body mass index in the full-heritage Pima Indians having a high rate of obesity has been reported [35].…”
Section: Discussionmentioning
confidence: 99%
“…A previous analytical study on plasma LPA in patients with acute coronary syndrome, showed that 18:2 LPA is produced by the lysoPLD action of ATX, whereas 20:4 LPA and 22:6 LPA are mainly derived from a platelet-related route and from unknown route, respectively. They also suggested lysophoshatidylethanolamine and LPG are possible as precursors of 20:4 LPA and 22:6 LPA, respectively [34], while it is uncertain why other molecular species of LPG were not converted to corresponding LPAs. In connection to these previous findings, our finding showing higher sensitivity to the dietary salt concentration of the 22:6 LPA plasma levels in both AA-treated and untreated rats should be mentioned.…”
Section: Discussionmentioning
confidence: 99%